Effects of Direction and Index of Difficulty on Aiming Movements after Stroke - Paola Ribeiro Coqueiro; Sandra Maria Sbeghen Ferreira de Freitas; Cassandra Mendes Assunção e Silva; Sandra Regina Alouche (Behavioural Neurology)
Background. Brain hemispheres play different roles in the control of aiming movements that are impaired after unilateral stroke. It is not clear whether those roles are influenced by the direction and the difficulty of the task. Objective. To evaluate the influence of direction and index of difficulty (ID) of the task on performance of ipsilesional aiming movements after unilateral stroke. Methods. Ten individuals with right hemisphere stroke, ten with left hemisphere stroke, and ten age- and gender-matched controls performed the aiming movements on a digitizing tablet as fast as possible. Stroke individuals used their ipsilesional arm. The direction (ipsilateral or contralateral), size (0.8 or 1.6 cm), and distance (9 or 18 cm) of the targets, presented on a monitor, were manipulated and determined to be of different ID (3.5, 4.5, and 5.5). Results. Individuals with right hemisphere lesion were more sensitive to ID of the task, affecting planning and final position accuracy. Left hemisphere lesion generated slower and less smooth movements and was more influenced by target distance. Contralateral movements and higher ID increased planning demands and hindered movement execution. Conclusion. Right and left hemisphere damages are differentially influenced by task constraints which suggest their complementary roles in the control of aiming movements.